Oxford manual of major incident management - Hunt, Paul, MD; Greaves, Ian (Oxford medical publications., 2017)
The 'Oxford Manual of Major Incident Management' brings together and integrates the key facts required by potential emergency responders and those involved in, the planning and preparation for, a major incident of any type or scale.